Recent economic evaluations of interventions to prevent cardiovascular disease by reducing sodium intake - Wang, Guijing (Curr Atheroscler Rep, 2013)
Excess intake of sodium, a common problem worldwide, is associated with hypertension and cardiovascular disease (CVD), while hypertension is a major risk factor for CVD. Population-wide efforts to reduce sodium intake have been identified as a promising strategy for preventing hypertension and CVD, and such initiatives are currently recommended by a variety of scientific and public health organizations. By reviewing the literature published from January 2011 to March 2013, we summarized recent economic evidence on interventions to reduce sodium intake. The evidence supports population-wide interventions for reducing sodium intake worldwide. Both lowering the salt content in manufactured foods and conducting mass media campaigns at national level are cost-effective in preventing CVD. Although better data on the cost of interventions is needed for rigorous economic evaluations, population-wide sodium reduction can be a promising approach for containing the growing health and economic burden associated with hypertension and its sequelae.